PENGARUH WAKTU PENGOCOKAN DAN KONSENTRASI XILANASE DARI Trichoderma viride TERHADAP XILANASE TERADSORPSI DAN AKTIVITAS XILANASE - Sutrisno, Sutrisno; Roosdiana, Anna; Larasati, Luckyta Retno (Jurnal Ilmu Kimia Universitas Brawijaya, 2015)
Xylanase was immobilized with physical adsorption method by using kaolin. Immobilization is conducted in order to increase efficiency of enzyme utilization so that it can be used repeatedly. The objective of this research is to determine agitation time and optimum xilanase concentration. This research consisted two treatments which agitation time of (1, 2, 3, 4, 5) hours and enzyme concentrations of (0.157 0.209, 0.261, 0.314, 0.366) mg/mL. Free xylanase was 0.366 mg/mL with activity 8.449 unit. The result showed that the optimum condition of immobilized xylanase on kaolin was obtained at 3 hours agitation with total adsorbed xylanase 4,74 mg/g resalting in xylanase actitity of 10.074 unit. Whereas the optimum xylanase concentration was 0.261 ppm yielding in xylanase activity of  14.336 unit.Keyword : Activity, Kaolin, Trichderma viride, Xylanase